Benzene Diazonium Sulfonate Modified Nanoporous Gold Electrodes for the Direct Detection of Copper(II) Ions. Issue 22 (17th November 2020) - Siepenkoetter, Till; Mastin, Hélène; Salaj‐Kosla, Urszula; Magner, Edmond
Abstract: The detection of Cu 2+ on surface modified nanoporous gold in aqueous solution is reported. Nanoporous gold electrodes were prepared with a wide range of pore sizes by dealloying of sputtered gold–silver alloys in concentrated nitric acid. Varying the pore sizes can significantly improve the electroactive surface area of the electrodes as well as protect the surface from biofouling materials, both necessary for the direct detection of trace metals in untreated samples. Two surface modifications i. e . a self‐assembled monolayer of 3‐mercapto‐1‐propanesulfonate and electro‐grafted benzene diazonium sulfonate were evaluated. Underpotential deposition of Cu 2+ and subsequent stripping of the deposited copper was achieved utilizing square wave voltammetry. The sensor was capable of accurately measuring Cu 2+ concentrations in a range of water samples (tap, rain and river water) without the necessity of prior pre‐treatment of the samples. The sensor had a linear range of 0.2 to 25 μM, which encompasses the accepted maximum limit for the concentration of copper in drinking water (20.5 μM). The sensitivity was 8.18 μA cm −2 μM −1 with a limit of detection of 18.9 nM (∼1.2 ppb). The response of the sensor in artificial human serum was unaffected by the sample matrix, demonstrating the ability of the system to resist fouling by serum Abstract : Copper sensing : A diazonium‐modified nanoporous gold electrode was prepared with a linear range of 0.2–25 μM and used for the accurate detection of Cu 2+ in water (tap, rain and river water) samples without the necessity of prior pre‐treatment. The response of the sensor in artificial human serum was unaffected by the sample matrix, demonstrating the ability of the system to resist fouling by serum.